Black entrepreneurship: a case study on entrepreneurial activities and ambitions in a South African township. Issue 3 (5th August 2014) - Preisendoerfer, Peter; Bitz, Ansgar; J. Bezuidenhout, Frans
Abstract : Purpose: – The purpose of this article is to investigate the current self-employment rate as well as entrepreneurial intentions of the township's population on the basis of an empirical case study of a single township. It is often assumed that the black population of South Africa (mostly living in townships) has a low participation rate in entrepreneurial activities and a low level of entrepreneurial ambitions. Besides the level of entrepreneurship, personal and socio-economic factors affecting participation in entrepreneurship are explored. Design/methodology/approach: – The article uses a face-to-face survey of about 350 adult residents of the township under investigation. Findings: – Contrary to the common assumption, entrepreneurial activity, which also includes all kinds of informal business ventures, cannot be qualified as low in the township under investigation. The same holds true for entrepreneurial ambitions, that is, people's intentions to start their own business in the near future. The factors influencing the probability of self-employment are similar to what we know from many other studies in the field of entrepreneurship. Socio-demographic attributes (gender, age), human capital factors (schooling, health) and social network resources (membership of organizations, self-employed friends) are significant predictors of entrepreneurial activity. It proves to be difficult, however, to explain who, in fact, articulates entrepreneurial ambitions. Practical implications: – The findings show that the basic prerequisites for expanding black entrepreneurship in South Africa are in place. Politically, it seems appropriate to initiate more public support programs for black entrepreneurship, as such programs can help to translate entrepreneurial ambitions into action. However, to stay realistic, the contribution of entrepreneurship to overcome the structural problems of deprivation and poverty of the black population of South Africa should not be overestimated. Originality/value: – The article is based on a careful survey in a township using a random sample. Given the rare access to a disadvantaged township community, the result that there is no evidence of "lack of entrepreneurial impetus" deserves scientific and political attention.